Variability of maize genotypes for grain carotenoid composition - Cardoso, Wilton Soares; Paes, Maria Cristina Dias; Galvão, João Carlos Cardoso; Rios, Sara de Almeida; Guimarães, Paulo Evaristo de Oliveira; Schaffert, Robert Eugene; Borém, Aluízio (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to characterize 134 maize (Zea mays) genotypes, for carotenoids content and build a genetic profile to facilitate future breeding to increase grain nutritional value (biofortification). Seeds came from experimental fields and from the Banco Ativo de Germoplasma of Embrapa Milho e Sorgo, Sete Lagoas, MG, Brazil. The genotypes were commercial hybrids, varieties, and inbred lines developed by the Embrapa biofortification program and other accessions, chosen for their yellow-orange endosperm color. Total grain carotenoids, carotenes, xanthophylls (monohydroxylates and dihydroxylates) were determined by chromatographic-spectrophotometric methods. The detected averages were: 22.34 µg g-1 for total carotenoids, 2.55 µg g-1 for carotenes, 3.86 μgág-1 for monohydroxylated xanthophylls, and 15.93 µg g-1 for dihydroxylated xanthophylls. The genotypes variability was divided into 18 groups by the method of Tocher. The Embrapa germplasm has variability and potential for development of maize lines biofortified for total of provitamin A carotenoids.